The consequences of household member incarceration on justice-involved youth - Hoover, Kaitlyn B. (Journal of crime and justice, 2022)
Household member incarceration has only increased in prevalence due to the era of mass incarceration; however prior studies have focused exclusively on the impacts of parental imprisonment. In an effort to expand the literature, the current study examines (1) whether having a household family member incarcerated leads to within-individual changes in offending and substance use over time and (2) whether these effects vary according to the type of family member who was incarcerated. Using the Pathways to Desistance Study, fixed effects negative binomial and Poisson regression models were performed on the sample of justice-involved adolescents and young adults. The findings demonstrate that experiencing any type of household member incarceration increases offending, drug use, and binge drinking behaviors. Moreover, a sibling incarceration effect was found in which experiencing sibling incarceration increased offending, drug use, and binge drinking behaviors. Additional findings and implications are discussed.